Biocontrol of Listeria monocytogenes and Salmonella Typhimurium in hydroponics: Evaluating the efficacy of plant growth promoting bioinoculants - Grace Akumu; Leslie D. Thompson; Mindy M. Brashears; Catherine R. Simpson; Christopher J. Currey; Angela M. Walla (Food Control, 2026)

Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Three decades of continuous warming in temperate forests destabilizes persistent forms of soil organic matter - Atzín X. San Román; Serita D. Frey; Melissa A. Knorr; Huan Tong; Jerry M. Melillo; Myrna J. Simpson (Science of The Total Environment, 2026)

N-Acetylcysteine Dose and Treatment Duration in High-Risk Acetaminophen Ingestions Treated Within Eight Hours: A Retrospective Cohort Study - C. James Watson; Michael D. Simpson; Nishita Saraiya; Christopher A. Wilkosz; Michael B. Yu; Michele M. Burns; Mark J. Neavyn; Karen E. Simone; Tania D. Strout (Journal of Medical Toxicology, 2026)
Introduction Toxicologists may use high dose n-acetylcysteine (HD-NAC) for early-treated high-risk acetaminophen ingestions (EHRAI) given concerns over standard NAC (S-NAC) dosing’s efficacy. We utilize the novel, clinically relevant outcome of mean additional 16-hour NAC maintenance infusions (NMI) to evaluate differences in treatment duration for EHRAI patients treated with S-NAC versus HD-NAC. Methods Retrospective multistate poison center study from 1/1/2019-7/4/2024 of patients ≥ 13-years-old who were treated with S-NAC or HD-NAC within eight hours of a high-risk acetaminophen ingestion. The primary outcome was mean additional NMI. Secondary outcomes were NAC infusion duration, hepatotoxicity, coagulopathy, transplant, and death. Sensitivity analyses evaluated for robustness of findings. Results Of 127 included cases, 52.0% (66/127) received HD-NAC. 7.1% (9/127) had anti-peristaltic co-ingestions. HD-NAC cases received more fomepizole (23.1% versus 1.6%; difference 21.1%). Acetaminophen concentrations controlled for time since ingestion were similar (mean acetaminophen ratio for HD-NAC: 2.7, IQR: 2.3, 3.3 versus S-NAC: 2.4, IQR: 2.2, 2.7; difference − 0.3). 26.0% (33/127) received NMI solely for residual detectable serum acetaminophen. There was no difference in mean additional NMI (HD-NAC: 0.53 versus S-NAC: 0.38; p = 0.240). Median NAC infusion durations were equal across groups (21.0; IQR: 21.0, 37.0; difference 0.0) ( p = 0.137). One patient per group developed hepatotoxicity; there were no transplants or deaths. Sensitivity analyses yielded similar results. Conclusions We found no difference in mean NMI for EHRAI based on NAC dose. These findings support additional NMI as an objective, common, clinically relevant outcome for acetaminophen toxicity research.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Calibration of WinSLAMM to stormwater volume and pollutant mass flux data in Ohio, USA: Informing pollutant loads in untreated stormwater from various urban land uses - Ian M. Simpson; Ryan J. Winston; Jay D. Dorsey (Journal of Hydrology, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Forest terpenes and stress: Examining the associations of filtered vs. non-filtered air in a real-life natural environment - Chaja M. Levy; Anne M. Riederer; Christopher D. Simpson; Amanda J. Gassett; Abigail J. Gilbert; Michael H. Paulsen; Lalith K. Silva; Deepak Bhandari; Cody A. Newman; Benjamin C. Blount; Peter H. Kahn; Gregory N. Bratman (Environmental Research, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Environmental and dietary factors associated with urinary OH-PAHs in mid-pregnancy in a large multi-site study - Anne M. Riederer; Allison R. Sherris; Adam A. Szpiro; Melissa M. Melough; Christopher D. Simpson; Christine T. Loftus; Drew B. Day; Erin R. Wallace; Leonardo Trasande; Emily S. Barrett; Ruby HN. Nguyen; Kurunthachalam Kannan; et al. (Environmental Research, 2025)

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Examining disparities in PFAS plasma concentrations: Impact of drinking water contamination, food access, proximity to industrial facilities and superfund sites - Shiwen Li; Jesse A. Goodrich; Elizabeth Costello; Douglas I. Walker; Carlos Cardenas-Iniguez; Jiawen Carmen Chen; Tanya L. Alderete; Damaskini Valvi; Sarah Rock; Sandrah P. Eckel; Rob McConnell; Frank D. Gilliland; et al. (Environmental Research, 2025)

Lionfish (Pterois volitans) do not show directional preferences for ambient underwater soundscapes during diurnal hours - Roxanne B Holmes; Nadia M. Hamilton; Stephen D. Simpson; James E. Herbert-Read (Marine Biology, 2025)
Sound is a valuable cue in the marine environment that can inform animals about habitat location and community composition. Indeed, sound is often used for orientation and navigation by larval reef fishes during settlement. However, despite sound’s role in the early life of reef fishes, whether post-settlement reef fishes use ambient soundscapes to inform their movement decisions remains less clear. In an in-situ playback experiment in Curaçao, the Dutch Caribbean, settled individuals of an invasive predator, the Indo-Pacific lionfish ( Pterois volitans ), showed no preference to move towards the playbacks of two different habitat types during daylight hours. In particular, lionfish did not prefer to move towards the sounds of sandy or reef habitat playbacks when tested against a silent control. Moreover, when given a choice between simultaneous sandy and reef habitat playbacks, lionfish showed no preference for the soundscape of either habitat type. While the activity of lionfish was strongly correlated with their body size, with larger fish being more active, activity was not affected by habitat playback, nor did body size affect their preference for the soundscapes of either habitat type. While acoustic lures have been speculated to be a promising addition to existing lionfish trap designs, daytime playbacks of ambient soundscapes are unlikely to be successful in attracting lionfish post-settlement, ultimately affecting their efficacy.

Half a century of citizen science tag-recapture data reveals stock delineation and cross-jurisdictional connectivity of an iconic pelagic fish - Belinda K. Goddard; Tristan A. Guillemin; Hayden T. Schilling; Julian M. Hughes; Stephanie Brodie; Corey P. Green; Robert Harcourt; Charlie Huveneers; Daniel Ierodiaconou; Iain M. Suthers; Matthew D. Taylor; Sean R. Tracey; et al. (Reviews in Fish Biology and Fisheries, 2024)
Tag-recapture programs to monitor the movements of fish populations are among some of the longest-running citizen-science datasets to date. Here, using half a century of yellowtail kingfish ( Seriola lalandi, Carangidae) tag-recapture data collected through citizen-science projects, we report novel insights into population connectivity in Australia and New Zealand (NZ). Despite the importance of kingfish in commercial and recreational fisheries, substantial knowledge gaps about their stock structure and connectivity between jurisdictions hinder current management efforts. Between 1974 and 2022, 63,432 releases and 4636 recaptures (7.3%) of tagged kingfish were collected in Australia and NZ. Most tagged individuals (51.4%) were recaptured within 10 km of their original release location up to 14 years post-release (mean: 225 days), indicating some degree of site fidelity. However, 656 (14.2%) kingfish were recaptured over 100 km from their release location, with one fish travelling at least 2834 km in 702 days. Seasonal variability was evident for releases and recaptures, with more releases occurring in summer and autumn in most jurisdictions. Network analysis of recaptures revealed no connectivity between tagged kingfish from western and eastern Australia, supporting genetic delineation. By contrast, extensive connectivity exists across eastern Australia and NZ, with 87 kingfish moving between five Australian state jurisdictions, 316 individuals travelling across 15 bioregions and six kingfish moving between Australia and NZ. Our findings provide important new insights into the structure and connectivity of the eastern Australia kingfish stock and suggest increased collaboration between state and international fisheries jurisdictions may support improved stock assessment and management.

Germline copy number variants and endometrial cancer risk - Cassie E. Stylianou; George A. R. Wiggins; Vanessa L. Lau; Joe Dennis; Andrew N. Shelling; Michelle Wilson; Peter Sykes; Frederic Amant; Daniela Annibali; Wout De Wispelaere; Douglas F. Easton; Peter A. Fasching; et al. (Human Genetics, 2024)
Known risk loci for endometrial cancer explain approximately one third of familial endometrial cancer. However, the association of germline copy number variants (CNVs) with endometrial cancer risk remains relatively unknown. We conducted a genome-wide analysis of rare CNVs overlapping gene regions in 4115 endometrial cancer cases and 17,818 controls to identify functionally relevant variants associated with disease. We identified a 1.22-fold greater number of CNVs in DNA samples from cases compared to DNA samples from controls ( p = 4.4 × 10 –63 ). Under three models of putative CNV impact (deletion, duplication, and loss of function), genome-wide association studies identified 141 candidate gene loci associated ( p < 0.01) with endometrial cancer risk. Pathway analysis of the candidate loci revealed an enrichment of genes involved in the 16p11.2 proximal deletion syndrome, driven by a large recurrent deletion (chr16:29,595,483-30,159,693) identified in 0.15% of endometrial cancer cases and 0.02% of control participants. Together, these data provide evidence that rare copy number variants have a role in endometrial cancer susceptibility and that the proximal 16p11.2 BP4-BP5 region contains 25 candidate risk gene(s) that warrant further analysis to better understand their role in human disease.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Response of Root Respiration to Warming and Nitrogen Addition Depends on Tree Species - T. J. Muratore; M. A. Knorr; M. J. Simpson; R. B. Stephens; R. P. Phillips; S. D. Frey (Global Change Biology, 2024)
Roots contribute a large fraction of CO 2 efflux from soils, yet the extent to which global change factors affect root‐derived fluxes is poorly understood. We investigated how red maple ( Acer rubrum ) and red oak ( Quercus rubra ) root biomass and respiration respond to long‐term (15 years) soil warming, nitrogen addition, or their combination in a temperate forest. We found that ecosystem root respiration was decreased by 40% under both single‐factor treatments (nitrogen addition or warming) but not under their combination (heated × nitrogen). This response was driven by the reduction of mass‐specific root respiration under warming and a reduction in maple root biomass in both single‐factor treatments. Mass‐specific root respiration rates for both species acclimated to soil warming, resulting in a 43% reduction, but were not affected by N addition or the combined heated × N treatment. Notably, the addition of nitrogen to warmed soils alleviated thermal acclimation and returned mass‐specific respiration rates to control levels. Oak roots contributed disproportionately to ecosystem root respiration despite the decrease in respiration rates as their biomass was maintained or enhanced under warming and nitrogen addition. In contrast, maple root respiration rates were consistently higher than oak, and this difference became critical in the heated × nitrogen treatment, where maple root biomass increased, contributing significantly more CO 2 relative to single‐factor treatments. Our findings highlight the importance of accounting for the root component of respiration when assessing soil carbon loss in response to global change and demonstrate that combining warming and N addition produces effects that cannot be predicted by studying these factors in isolation.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Crustal architecture and tectonic development of western Queensland, Australia, based on deep seismic reflection profiling: Implications for Proterozoic continental assembly and dispersal - Russell J. Korsch; Michael P. Doublier; Dominic D. Brown; Janelle M. Simpson; Andrew J. Cross; Ross D. Costelloe; Wenping Jiang (Tectonophysics, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Evaluating the trophic transfer of PCBs from fish to humans: Insights from a synergism of environmental monitoring and physiologically-based pharmacokinetic modeling - Adam M. Simpson; Samuel A. Nutile; Olivia C. Hodgson; Ashley E. Russell; Jeremiah D. Keyes; Cody C. Wood; Ronald J. Buckanovich (Environmental Pollution, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

One step antimicrobial coatings for medical device applications based on low fouling polymers containing selenium nanoparticles - Fanyi Li; Tao Huang; Paul Pasic; Christopher D. Easton; Nicolas H. Voelcker; Daniel E. Heath; Neil M. O'Brien-Simpson; Andrea J. O'Connor; Helmut Thissen (Chemical Engineering Journal, 2023)

Hydrologic responses of single land use urban and forested watersheds and their implications to improving urban drainage design - Ian M. Simpson; Ryan J. Winston; R. Andrew Tirpak; Jay D. Dorsey; James H. Stagge; Jon M. Hathaway (Journal of Hydrology, 2023)

SCUBA noise alters community structure and cooperation at Pederson’s cleaner shrimp cleaning stations - Kieran P. McCloskey; Andrew N. Radford; Amelia Rose; Giorgio Casiraghi; Natalie Lubbock; Emma Weschke; Benjamin M. Titus; Dan A. Exton; Stephen D. Simpson (Frontiers in Marine Science, 2023)
Recreational SCUBA diving is widespread and increasing on coral reefs worldwide. Standard open-circuit SCUBA equipment is inherently noisy and, by seeking out areas of high biodiversity, divers inadvertently expose reef communities to an intrusive source of anthropogenic noise. Currently, little is known about SCUBA noise as an acoustic stressor, and there is a general lack of empirical evidence on community-level impacts of anthropogenic noise on coral reefs. Here, we conducted a playback experiment on Caribbean reefs to investigate impacts of SCUBA noise on fish communities and interspecific cooperation at ecologically important cleaning stations of the Pederson’s cleaner shrimp Ancylomenes pedersoni . When exposed to SCUBA-noise playback, the total occurrence of fishes at the cleaning stations decreased by 7%, and the community and cleaning clientele compositions were significantly altered, with 27% and 25% of monitored species being affected, respectively. Compared with ambient-sound playback, SCUBA-noise playback resulted in clients having to wait 29% longer for cleaning initiation and receiving 43% less cleaning; however, cheating, signalling, posing and time spent cleaning were not affected by SCUBA-noise playback. Our study is the first to demonstrate experimentally that SCUBA noise can have at least some negative impacts on reef organisms, confirming it as an ecologically relevant pollutant. Moreover, by establishing acoustic disturbance as a likely mechanism for known impacts of diver presence on reef animals, we also identify a potential avenue for mitigation in these valuable ecosystems.

A metagenomic-based study of two sites from the Barbadian reef system - S. Simpson; V. Bettauer; A. Ramachandran; S. Kraemer; S. Mahon; M. Medina; Y. Vallès; V. Dumeaux; H. Vallès; D. Walsh; M. T. Hallett (Coral Reefs, 2023)
We study the microbiome of sea water collected from two locations of the Barbadian coral reefs. The two sites differ in several environmental and ecological variables including their endogenous benthic community and their proximity to urban development and runoffs from inland watersheds. The composition of the microbial communities was estimated using whole genome DNA shotgun sequencing with adjuvant measurements of chemical and environmental qualities. Although both sites exhibit a similar degree of richness, the less urbanized site (Maycocks reef at Hangman’s Bay) has a strong concentration of phototrophs whereas the more urbanized location (Bellairs reef at Folkstone) is enriched for copiotrophs, macroalgal symbionts and marine-related disease-bearing organisms from taxa scattered across the tree of life. Our results are concordant with previous profiles of warm ocean surface waters, suggesting our approach captures the state of each coral reef site, setting the stage for longitudinal studies of marine microbiome dynamics in Barbados.

Marine invertebrates and noise - Marta Solé; Kenzo Kaifu; T. Aran Mooney; Sophie L. Nedelec; Frédéric Olivier; Andrew N. Radford; Mirella Vazzana; Matthew A. Wale; Jayson M. Semmens; Stephen D. Simpson; Giuseppa Buscaino; Anthony Hawkins; et al. (Frontiers in Marine Science, 2023)
Within the set of risk factors that compromise the conservation of marine biodiversity, one of the least understood concerns is the noise produced by human operations at sea and from land. Many aspects of how noise and other forms of energy may impact the natural balance of the oceans are still unstudied. Substantial attention has been devoted in the last decades to determine the sensitivity to noise of marine mammals—especially cetaceans and pinnipeds—and fish because they are known to possess hearing organs. Recent studies have revealed that a wide diversity of invertebrates are also sensitive to sounds, especially via sensory organs whose original function is to allow maintaining equilibrium in the water column and to sense gravity. Marine invertebrates not only represent the largest proportion of marine biomass and are indicators of ocean health but many species also have important socio-economic values. This review presents the current scientific knowledge on invertebrate bioacoustics (sound production, reception, sensitivity), as well as on how marine invertebrates are affected by anthropogenic noises. It also critically revisits the literature to identify gaps that will frame future research investigating the tolerance to noise of marine ecosystems.

Monitoring the effects of urban and forested land uses on runoff quality: Implications for improved stormwater management - Ian M. Simpson; Ryan J. Winston; Jay D. Dorsey (Science of The Total Environment, 2023)

Optimization and Scale Up of Spray Dried CPZEN-45 Aerosol Powders for Inhaled Tuberculosis Treatment - Ian E. Stewart; Phillip G. Durham; Jacob M. Sittenauer; Aranza P. Barreda; Grayson W. Stowell; Carmella Moody; Jeffery B. Mecham; Catherine Simpson; Sharon Daily; Sara E. Maloney; Mark D. Williams; Diana Severynse-Stevens; et al. (Pharmaceutical Research, 2022)

Warfarin Overdose in an Adolescent Not Dependent on Anticoagulation: Reversal Strategy and Kinetics - C. James Watson; Michael D. Simpson; James D. Whitledge; Al Patterson; Michele M. Burns (Journal of Medical Toxicology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Anthropogenic Mixing in Seasonally Stratified Shelf Seas by Offshore Wind Farm Infrastructure - Robert M. Dorrell; Charlie J. Lloyd; Ben J. Lincoln; Tom P. Rippeth; John R. Taylor; Colm-cille P. Caulfield; Jonathan Sharples; Jeff A. Polton; Brian D. Scannell; Deborah M. Greaves; Rob A. Hall; John H. Simpson (Frontiers in Marine Science, 2022)
The offshore wind energy sector has rapidly expanded over the past two decades, providing a renewable energy solution for coastal nations. Sector development has been led in Europe, but is growing globally. Most developments to date have been in well-mixed, i.e., unstratified, shallow-waters near to shore. Sector growth is, for the first time, pushing developments to deep water, into a brand new environment: seasonally stratified shelf seas. Seasonally stratified shelf seas, where water density varies with depth, have a disproportionately key role in primary production, marine ecosystem and biogeochemical cycling. Infrastructure will directly mix stratified shelf seas. The magnitude of this mixing, additional to natural background processes, has yet to be fully quantified. If large enough it may erode shelf sea stratification. Therefore, offshore wind growth may destabilize and fundamentally change shelf sea systems. However, enhanced mixing may also positively impact some marine ecosystems. This paper sets the scene for sector development into this new environment, reviews the potential physical and environmental benefits and impacts of large scale industrialization of seasonally stratified shelf seas and identifies areas where research is required to best utilize, manage, and mitigate environmental change.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Mineralogical and Micro-structural Investigation into the Mechanical Behaviour of a Soft Calcareous Mudstone - D. Simpson; M. Rouainia; G. Elia (Rock Mechanics and Rock Engineering, 2021)
The construction industry in Abu Dhabi is thriving and its coastline has some of the most ambitious structures in the world. Whilst the subsurface evaporitic and calcareous soft rocks of this region are of great geological interest, they are relatively poorly understood from a geotechnical engineering perspective, forcing foundation designs to be overly conservative. Understanding the stiffness of the underlying geology at small strains is of great importance for the accurate estimation of ground movements around excavations and foundations, and yet routine post-SI laboratory testing programmes tend to focus on basic rock mechanics tests such as UCS tests. These procedures are generally unsuitable for use with calcareous rocks due to their friable and moisture sensitive nature, and rarely obtain parameters representative of actual in situ behaviour. The calcareous mudstone investigated in this paper has mechanical and structural characteristics falling between those of a soil and those typical of a rock and, as such, requires a geotechnical testing approach that combines methods from both soil and rock mechanics disciplines. The mineralogical, micro-structural and mechanical characteristics of this lithology have been examined via a suite of testing techniques, including XRPD, SEM, advanced triaxial with bender elements, along with industry standard procedures. Shearing, tensile and consolidation behaviours have been explored. Examination of the micro- and macro-scale features of this material shows it to be highly structured, with strength and stiffness being controlled by inter-granular bonding of Dolomite grains, as well as by mean effective stress state and rate of strain. The presence of fibrous Palygorskite acts to reduce the degree of bonding, causing specimens rich in this clay mineral to have a more ductile mechanical behaviour.

Zircon petrochronology in large igneous provinces reveals upper crustal contamination processes: new U–Pb ages, Hf and O isotopes, and trace elements from the Central Atlantic magmatic province (CAMP) - J. H. F. L. Davies; A. Marzoli; H. Bertrand; N. Youbi; M. Ernesto; N. D. Greber; M. Ackerson; G. Simpson; A.-S. Bouvier; L. Baumgartner; T. Pettke; F. Farina; et al. (Contributions to Mineralogy and Petrology, 2021)
Zircon occasionally crystallizes in evolved melt pockets in mafic large igneous province (LIP) magmas, and in these cases, it is used to provide high-precision age constraints on LIP events. The precision and accuracy of high-precision ages from LIPs are crucially important, because they may be implicated in mass extinctions. However, why zircon crystallizes in these magmas is not clearly understood, since their mafic compositions should limit zircon saturation. Here, we investigate the occurrence of zircon (and baddeleyite) in intrusive and extrusive mafic rocks from Central Atlantic Magmatic Province (CAMP) using petrography, trace-element analysis, Ti temperatures, Hf and oxygen isotopes, and high-precision U–Pb geochronology, along with petrological and thermal modeling. We provide new ages for CAMP sills that intruded into Paleozoic sediments in Brazil, indicating that the high and low Ti magmatism in this area occurred synchronously over 264 ± 57 ka. We show that upper crustal assimilation, especially of shales, during the emplacement of the CAMP likely led to zircon saturation. Assimilation of upper crustal sediments is also supported by high δ 18 O values and some rare negative εHf values in the zircon crystals. The only extrusive sample analyzed was the North Mountain basalt in Nova Scotia, Canada. This sample contains a large age variation in its zircon crystals (up to 4 Ma), and the older crystals have slightly more negative εHf values suggesting the presence of small (micron scale) xenocrystic cores associated with very late-stage sediment assimilation. However, the CAMP dataset as a whole suggests that the presence of xenocrystic cores is rare. Assuming no xenocrystic cores, and considering the zircon undersaturated nature of LIP mafic melts, the oldest zircon age clusters in a population should record the magma emplacement (or time when assimilation occurred), and the younger ages in a population are more likely to reflect Pb loss, especially given the high U concentrations of LIP zircon. Our identification of heterogeneous isotopic and elemental compositions in LIP zircon indicates that zircon in these magmas saturate in isolated minute melt pockets just before the system cools below its solidus.

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Energetic Carrying Capacity of Submersed Aquatic Vegetation in Semi-Permanent Wetlands Important to Waterfowl in the Upper Midwest - Margaret C. Gross; Joseph D. Lancaster; John W. Simpson; Brendan T. Shirkey; Sarah E. McClain; Christopher N. Jacques; J. Brian Davis; Heath M. Hagy (Wetlands, 2020)

A case of aberrant CD8 T cell–restricted IL-7 signaling with a Janus kinase 3 defect–associated atypical severe combined immunodeficiency - Aaruni Khanolkar; Jeffrey D. Wilks; Guorong Liu; Bridget M. Simpson; Edward A. Caparelli; Dawn A. Kirschmann; Jenna Bergerson; Ramsay L. Fuleihan (Immunologic Research, 2020)

Cerebrospinal Fluid Ceruloplasmin, Haptoglobin, and Vascular Endothelial Growth Factor Are Associated with Neurocognitive Impairment in Adults with HIV Infection - A. R. Kallianpur; H. Gittleman; S. Letendre; R. Ellis; J. S. Barnholtz-Sloan; W. S. Bush; R. Heaton; D. C. Samuels; D. R. Franklin; D. Rosario-Cookson; D. B. Clifford; A. C. Collier; et al. (Molecular Neurobiology, 2019)

Fishes in a changing world: learning from the past to promote sustainability of fish populations - T. A. C. Gordon; H. R. Harding; F. K. Clever; I. K. Davidson; W. Davison; D. W. Montgomery; R. C. Weatherhead; F. M. Windsor; J. D. Armstrong; A. Bardonnet; E. Bergman; J. R. Britton; et al. (Journal of Fish Biology, 2018)
Populations of fishes provide valuable services for billions of people, but face diverse and interacting threats that jeopardize their sustainability. Human population growth and intensifying resource use for food, water, energy and goods are compromising fish populations through a variety of mechanisms, including overfishing, habitat degradation and declines in water quality. The important challenges raised by these issues have been recognized and have led to considerable advances over past decades in managing and mitigating threats to fishes worldwide. In this review, we identify the major threats faced by fish populations alongside recent advances that are helping to address these issues. There are very significant efforts worldwide directed towards ensuring a sustainable future for the world's fishes and fisheries and those who rely on them. Although considerable challenges remain, by drawing attention to successful mitigation of threats to fish and fisheries we hope to provide the encouragement and direction that will allow these challenges to be overcome in the future.

Molecular tools for bathing water assessment in Europe: Balancing social science research with a rapidly developing environmental science evidence-base - David M. Oliver; Nick D. Hanley; Melanie van Niekerk; David Kay; A. Louise Heathwaite; Sharyl J. M. Rabinovici; Julie L. Kinzelman; Lora E. Fleming; Jonathan Porter; Sabina Shaikh; Rob Fish; Sue Chilton; et al. (Ambio, 2016)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Variation in toxicity of a current-use insecticide among resurrected Daphnia pulicaria genotypes - Adam M. Simpson; Punidan D. Jeyasingh; Jason B. Belden (Ecotoxicology, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Brain morphometric correlates of metabolic variables in HIV: the CHARTER study - S. L. Archibald; J. A. McCutchan; C. Sanders; T. Wolfson; T. L. Jernigan; R. J. Ellis; B. M. Ances; A. C. Collier; J. C. McArthur; S. Morgello; D. M. Simpson; C. Marra; et al. (Journal of NeuroVirology, 2014)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Increases in brain white matter abnormalities and subcortical gray matter are linked to CD4 recovery in HIV infection - Christine Fennema-Notestine; Ronald J. Ellis; Sarah L. Archibald; Terry L. Jernigan; Scott L. Letendre; Randy J. Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; David J. Croteau; Tanya Wolfson; Robert K. Heaton; et al. (Journal of NeuroVirology, 2013)

Vertical and horizontal distributions of coral‐reef fish larvae in open water immediately prior to reef colonization - D. Lecchini; V. P. Waqalevu; S. Holles; M. Lerohellec; C. Brie; S. D. Simpson (Journal of Fish Biology, 2013)
To explore the vertical and horizontal distributions of fish larvae near the end of their pelagic period, six light traps were set up over four lunar months at different depths (sub‐surface, midwater and bottom) and different habitat types (reef slope: 50 m horizontal distance from the reef crest; frontier zone: 110 m horizontal distance; sandy zone: 200 m horizontal distance) on the outer reef slope of Moorea Island, French Polynesia. The highest captures were in sub‐surface traps on the reef slope and the frontier zone, and in bottom traps on the sandy zone and the frontier zone. It is hypothesized that fish larvae move towards the surface near the reef slope to avoid reef‐based planktivores and to get into a favourable position for surfing over the reef crest.

Apolipoprotein E4 genotype does not increase risk of HIV-associated neurocognitive disorders - E. E. Morgan; S. P. Woods; S. L. Letendre; D. R. Franklin; C. Bloss; A. Goate; R. K. Heaton; A. C. Collier; C. M. Marra; B. B. Gelman; J. C. McArthur; S. Morgello; et al. (Journal of NeuroVirology, 2013)

Considerations for modeling burn probability across landscapes with steep environmental gradients: an example from the Columbia Mountains, Canada - Marc-André Parisien; Gregg R. Walker; John M. Little; Brian N. Simpson; Xianli Wang; Daniel D. B. Perrakis (Natural Hazards, 2013)

Editorial for the Special Issue for the 3rd Modern Solid Phase Peptide Synthesis and its Applications Symposium - Neil M. O’Brien-Simpson; John D. Wade (International Journal of Peptide Research and Therapeutics, 2013)

Mitochondrial DNA variation and HIV-associated sensory neuropathy in CHARTER - Emily R. Holzinger; Todd Hulgan; Ronald J. Ellis; David C. Samuels; Marylyn D. Ritchie; David W. Haas; Asha R. Kallianpur; Cinnamon S. Bloss; David B. Clifford; Ann C. Collier; Benjamin B. Gelman; Christina M. Marra; et al. (Journal of NeuroVirology, 2012)

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

Notes on the health status of free-living, non-native American mink, Neovison vison, in southern England - L. A. Harrington; M. Gelling; V. Simpson; A. Harrington; D. W. Macdonald (European Journal of Wildlife Research, 2012)

Large scale international replication and meta-analysis study confirms association of the 15q14 locus with myopia. The CREAM consortium - Virginie J. M. Verhoeven; Pirro G. Hysi; Seang-Mei Saw; Veronique Vitart; Alireza Mirshahi; Jeremy A. Guggenheim; Mary Frances Cotch; Kenji Yamashiro; Paul N. Baird; David A. Mackey; Robert Wojciechowski; M. Kamran Ikram; et al. (Human Genetics, 2012)

The impact of 6-month training preparation for an Ironman triathlon on the proportions of naïve, memory and senescent T cells in resting blood - Cormac Cosgrove; Stuart D. R. Galloway; Craig Neal; Angus M. Hunter; Brian K. McFarlin; Guilllaume Spielmann; Richard J. Simpson (European Journal of Applied Physiology, 2012)

Effects of long-term grassland management on the chemical nature and bioavailability of soil phosphorus - Meg Simpson; Roger D. McLenaghen; Ivan Chirino-Valle; Leo M. Condron (Biology and Fertility of Soils, 2012)

A doxycycline-inducible, tissue-specific aromatase-expressing transgenic mouse - Jenny D. Y. Chow; John T. Price; Margaret M. Bills; Evan R. Simpson; Wah Chin Boon (Transgenic Research, 2012)

Genetic features of cerebrospinal fluid-derived subtype B HIV-1 tat - Jun Yong Choi; George K. Hightower; Joseph K. Wong; Robert Heaton; Steven Woods; Igor Grant; Thomas D. Marcotte; Ronald J. Ellis; Scott L. Letendre; Ann C. Collier; Christina M. Marra; David B. Clifford; et al. (Journal of NeuroVirology, 2012)

Associations of whole-blood fatty acids and dietary intakes with prostate cancer in Jamaica - Maria D. Jackson; Susan P. Walker; Candace M. Simpson-Smith; Carole M. Lindsay; Garret Smith; Norma McFarlane-Anderson; Franklyn I. Bennett; Kathleen C. M. Coard; William D. Aiken; Trevor Tulloch; Tomlin J. Paul; Robert L. Wan (Cancer Causes & Control, 2012)

A test of the senses: Fish select novel habitats by responding to multiple cues - Chantal M. Huijbers; Ivan Nagelkerken; Pauline A. C. Lössbroek; Ines E. Schulten; Andjin Siegenthaler; Marc W. Holderied; Stephen D. Simpson (Ecology, 2012)
Habitat‐specific cues play an important role in orientation for animals that move through a mosaic of habitats. Environmental cues can be imprinted upon during early life stages to guide later return to adult habitats, yet many species must orient toward suitable habitats without previous experience of the habitat. It is hypothesized that multiple sensory cues may enable animals to differentiate between habitats in a sequential order relevant to the spatial scales over which the different types of information are conveyed, but previous research, especially for marine organisms, has mainly focused on the use of single cues in isolation. In this study, we investigated novel habitat selection through the use of three different sensory modalities (hearing, vision, and olfaction). Our model species, the French grunt, Haemulon flavolineatum , is a mangrove/seagrass‐associated reef fish species that makes several habitat transitions during early life. Using several in situ and ex situ experiments, we tested the response of fish toward auditory, olfactory, and visual cues from four different habitats (seagrass beds, mangroves, rubble, and coral reef). We identified receptivity to multiple sensory cues during the same life phase, and found that different cues induced different reactions toward the same habitat. For example, early‐juvenile fish only responded to sound from coral reefs and to chemical cues from mangroves/seagrass beds, while visual cues of conspecifics overruled olfactory cues from mangrove/seagrass water. Mapping these preferences to the ecology of ontogenetic movements, our results suggest sequential cue use would indeed aid successful orientation to novel key habitats in early life.

Enzymatic Characterisation of USP7 Deubiquitinating activity and Inhibition - Jonathan D. Wrigley; Kay Eckersley; Ian M. Hardern; Lindsey Millard; Michael Walters; Stephen W. Peters; Richard Mott; Thorsten Nowak; Richard A. Ward; Peter B. Simpson; Kevin Hudson (Cell Biochemistry and Biophysics, 2011)

Clinical factors related to brain structure in HIV: the CHARTER study - Terry L. Jernigan; Sarah L. Archibald; Christine Fennema-Notestine; Michael J. Taylor; Rebecca J. Theilmann; Michelle D. Julaton; Randy J. Notestine; Tanya Wolfson; Scott L. Letendre; Ronald J. Ellis; Robert K. Heaton; Anthony C. Gamst; et al. (Journal of NeuroVirology, 2011)

Temporal change in UK marine communities: trends or regime shifts? - M. Spencer; S. N. R. Birchenough; N. Mieszkowska; L. A. Robinson; S. D. Simpson; M. T. Burrows; E. Capasso; P. Cleall‐Harding; J. Crummy; C. Duck; D. Eloire; M. Frost; et al. (Marine Ecology, 2011)
A regime shift is a large, sudden, and long‐lasting change in the dynamics of an ecosystem, affecting multiple trophic levels. There are a growing number of papers that report regime shifts in marine ecosystems. However, the evidence for regime shifts is equivocal, because the methods used to detect them are not yet well developed. We have collated over 300 biological time series from seven marine regions around the UK, covering the ecosystem from phytoplankton to marine mammals. Each time series consists of annual measures of abundance for a single group of organisms over several decades. We summarised the data for each region using the first principal component, weighting either each time series or each biological component ( e.g. plankton, fish, benthos) equally. We then searched for regime shifts using Rodionov’s regime shift detection (RSD) method, which found regime shifts in the first principal component for all seven marine regions. However, there are consistent temporal trends in the data for six of the seven regions. Such trends violate the assumptions of RSD. Thus, the regime shifts detected by RSD in six of the seven regions are likely to be artefacts caused by temporal trends. We are therefore developing more appropriate time series models for both single populations and whole communities that will explicitly model temporal trends and should increase our ability to detect true regime shift events.

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Vegetative reproduction facilitates early expansion of Phyla canescens in a semi-arid floodplain - J. N. Price; M. J. Macdonald; C. L. Gross; R. D. B. Whalley; I. H. Simpson (Biological Invasions, 2011)

Functional alpha-1B adrenergic receptors on human epicardial coronary artery endothelial cells - Brian C. Jensen; Philip M. Swigart; Megan D. Montgomery; Paul C. Simpson (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

Editorial for the Special Issue on the 2nd Modern Solid Phase Peptide Synthesis and its Applications Symposium - Neil M. O’Brien-Simpson; John D. Wade (International Journal of Peptide Research and Therapeutics, 2010)

Buoyancy-stirring interactions in a subtropical embayment: a synthesis of measurements and model simulations in Maputo Bay, Mozambique - J D Lencart e Silva; J H Simpson; A M Hoguane; J-L Harcourt-Baldwin (African Journal of Marine Science, 2010)

Body size and risk of prostate cancer in Jamaican men - Maria D. Jackson; Susan P. Walker; Candace M. Simpson; Norma McFarlane-Anderson; Franklyn I. Bennett; Kathleen C. M. Coard; William D. Aiken; Trevor Tulloch; Tomlin J. Paul; Robert L. Wan (Cancer Causes & Control, 2010)

Fuirena bidgoodae, a new species of Cyperaceae from East Africa - K. Hoenselaar; A. M. Muasya; D. A. Simpson (Kew Bulletin, 2009)

Restoring depleted coral‐reef fish populations through recruitment enhancement: a proof of concept - A. Heenan; S. D. Simpson; M. G. Meekan; S. D. Healy; V. A. Braithwaite (Journal of Fish Biology, 2009)
To determine whether enhancing the survival of new recruits is a sensible target for the restorative management of depleted coral‐reef fish populations, settlement‐stage ambon damsel fish Pomacentrus amboinensis were captured, tagged and then either released immediately onto small artificial reefs or held in aquaria for 1 week prior to release. Holding conditions were varied to determine whether they affected survival of fish: half the fish were held in bare tanks (non‐enriched) and the other half in tanks containing coral and sand (enriched). Holding fish for this short period had a significantly positive effect on survivorship relative to the settlement‐stage treatment group that were released immediately. The enrichment of holding conditions made no appreciable difference on the survival of fish once released onto the reef. It did, however, have a positive effect on the survival of fish while in captivity, thus supporting the case for the provision of simple environmental enrichment in fish husbandry. Collecting and holding settlement‐stage fish for at least a week before release appear to increase the short‐term survival of released fish; whether it is an effective method for longer‐term enhancement of locally depleted coral‐reef fish populations will require further study.

Adiaspiromycosis Due to Emmonsia crescens is Widespread in Native British Mammals - Andrew M. Borman; Vic R. Simpson; Michael D. Palmer; Christopher J. Linton; Elizabeth M. Johnson (Mycopathologia, 2009)

Renal injury at first presentation as a predictor for poor outcome in severe paracetamol poisoning referred to a liver transplant unit - N. Pakravan; K. J. Simpson; W. S. Waring; C. M. Bates; D. N. Bateman (European Journal of Clinical Pharmacology, 2009)

Modern Solid Phase Peptide Synthesis and its Applications - Neil M. O’Brien-Simpson; Nicholas J. Ede; John D. Wade (International Journal of Peptide Research and Therapeutics, 2008)

Urban geochemistry: research strategies to assist risk assessment and remediation of brownfield sites in urban areas - I. Thornton; M. E. Farago; C. R. Thums; R. R. Parrish; R. A. R. McGill; N. Breward; N. J. Fortey; P. Simpson; S. D. Young; A. M. Tye; N. M. J. Crout; R. L. Hough; et al. (Environmental Geochemistry and Health, 2008)

Taxonomic novelties in Rhynchospora (Cyperaceae) from South America - A. C. Araújo; H. M. Longhi-Wagner; W. W. Thomas; D. A. Simpson (Kew Bulletin, 2008)

Alpha e-taxonomy: responses from the systematics community to the biodiversity crisis - S. J. Mayo; R. Allkin; W. Baker; V. Blagoderov; I. Brake; B. Clark; R. Govaerts; C. Godfray; A. Haigh; R. Hand; K. Harman; M. Jackson; et al. (Kew Bulletin, 2008)

Nocturnal relocation of adult and juvenile coral reef fishes in response to reef noise - S. D. Simpson; A. Jeffs; J. C. Montgomery; R. D. McCauley; M. G. Meekan (Coral Reefs, 2008)

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

A role for mu opioid receptors in cocaine-induced activity, sensitization, and reward in the rat - Joseph A. Schroeder; Michele Hummel; Alpha D. Simpson; Rizwan Sheikh; Avery R. Soderman; Ellen M. Unterwald (Psychopharmacology, 2007)

Effects of Light on Microalgae Concentrations and Selenium Uptake in Bivalves Exposed to Selenium-Amended Sediments - D. Schlenk; G. Batley; C. King; J. Stauber; M. Adams; S. Simpson; W. Maher; J. T. Oris (Archives of Environmental Contamination and Toxicology, 2007)

Bushiness and cytokinin profile in dormant and sprouting tubers of Zantedeschia - S. M. D’Arth; S. I. Simpson; J. F. Seelye; P. E. Jameson (Plant Cell, Tissue and Organ Culture (PCTOC), 2007)

An enhanced microsatellite map of diploid Fragaria - D. J. Sargent; J. Clarke; D. W. Simpson; K. R. Tobutt; P. Arús; A. Monfort; S. Vilanova; B. Denoyes-Rothan; M. Rousseau; K. M. Folta; N. V. Bassil; N. H. Battey (Theoretical and Applied Genetics, 2006)

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

Comparison of reference genes for quantitative real-time polymerase chain reaction analysis of gene expression in sugarcane - Hayati M. Iskandar; Robert S. Simpson; Rosanne E. Casu; Graham D. Bonnett; Donald J. Maclean; John M. Manners (Plant Molecular Biology Reporter, 2004)

A genetic linkage map of microsatellite, gene-specific and morphological markers in diploid Fragaria - D. J. Sargent; T. M. Davis; K. R. Tobutt; M. J. Wilkinson; N. H. Battey; D. W. Simpson (Theoretical and Applied Genetics, 2004)

An Assessment of Five Australian Polychaetes and Bivalves for Use in Whole-Sediment Toxicity Tests: Toxicity and Accumulation of Copper and Zinc from Water and Sediment - C. K. King; M. C. Dowse; S. L. Simpson; D. F. Jolley (Archives of Environmental Contamination and Toxicology, 2004)

Role of the Land Plume in the Transport of Ozone Over the Ocean During Indoex (1999) - M. D. Simpson; S. Raman (Boundary-Layer Meteorology, 2004)

Do early life history characteristics determine species ranges and dispersal of coral reef fishes in the Indo‐Pacific? - M. A. Priest; S. D. Simpson; C. Dytham (Journal of Fish Biology, 2003)
The Indo‐Pacific consists of extensive continuous coastlines and many island groups of varying sizes and isolation. The species ranges of coral reef fishes vary enormously from Indo‐Pacific wide to highly endemic. There is also great variation in the early life history characteristics of coral reef fishes ( e.g . pelagic larval durations, spawning strategies and swimming abilities). We use individual‐based models (IBMs) to simulate the dispersal of coral reef fishes in the Indo‐Pacific. The development of dispersal strategies is explored based on ecological and geographical constraints. Simulations are presented for climatic and anthropogenically‐induced events.

Does behaviour explain the larval dispersal of coral reef fishes better than oceanography?– An individual based model simulation approach - S. D. Simpson; C. Dytham; M. G. Meekan (Journal of Fish Biology, 2003)
Until recently, oceanographic models have been used, with limited success, to predict the larval dispersal of coral reef fishes. Settlement‐stage larvae have been shown to be capable swimmers and have highly developed sensory organs. We built two simulation individual based models (IBMs) of larval dispersal in the Dampier Archipelago, Western Australia. One followed an oceanographic model, while the other was driven by behavioural constraints. We compare predictions of these models with an extensive dataset from a light‐trapping programme in an attempt to elucidate the overriding mechanism of larval coral reef fish dispersal.

Characteristics of an ozone deposition module II: Sensitivity analysis - D. Simpson; J.-P. Tuovinen; L. Emberson; M. R. Ashmore (Water, Air, & Soil Pollution, 2003)

Plant collecting spread and densities: their potential impact on biogeographical studies in Thailand - J. A. N. Parnell; D. A. Simpson; J. Moat; D. W. Kirkup; P. Chantaranothai; P. C. Boyce; P. Bygrave; S. Dransfield; M. H. P. Jebb; J. Macklin; C. Meade; D. J. Middleton; et al. (Journal of Biogeography, 2003)
Aims To produce representative aggregate maps of plant collection locations in Thailand and discuss their impact on biogeographical studies in Thailand and the surrounding region. Location Thailand. Methods A representative data set comprising 6593 plant specimen records for Thailand has been assembled. The data set contains ± all known collections for fifteen representative plant families and further records for another 104. All records are localized to Changwat (province), 6441 to at least quarter degree square. Results Analysis shows that the spread of collecting activity in Thailand is markedly uneven; 20% of collections come from a single Changwat (Chiang Mai) and 53% of Changwat have fifty or fewer collections. The distribution of collections by Changwat and by quarter degree square is erratic with most squares and Changwat having few collections, both in proportionate and absolute terms. Some of the most densely forested Changwats and squares appear undercollected. Distribution maps for common, easily recognized tree species in the genus Syzygium show distributional gaps. Conclusions Thailand is defined as an undercollected country. Even within the few well‐collected quarter degree squares the spread of collecting is still poor; almost all collections being localized to one of three mountain ranges or their foothills. There are many gaps in collecting activity which make impossible a straightforward interpretation of biogeographical pattern. It is argued that targeted collecting activity is needed, that assembly of this type of data set is therefore essential and that our data set and its interpretation is a model for all countries in the region.

Microphysics, radiation and surface processes in the Goddard Cumulus Ensemble (GCE) model - Wei-Kuo Tao; J. Simpson; D. Baker; S. Braun; M.-D. Chou; B. Ferrier; D. Johnson; A. Khain; S. Lang; B. Lynn; C.-L. Shie; D. Starr; et al. (Meteorology and Atmospheric Physics, 2003)

Bushiness and cytokinin sensitivity in micropropagated Zantedeschia - Suzanne M. D'Arth; Sandra I. Simpson; John F. Seelye; Paula E. Jameson (Plant Cell, Tissue and Organ Culture (PCTOC), 2002)

Coherence between one random and one periodic signal for measuring the strength of responses in the electro-encephalogram during sensory stimulation - A. M. F. L. Miranda de Sá; A. F. C. Infantosi; D. M. Simpson (Medical & Biological Engineering & Computing, 2002)

Telescoped porphyry Cu-Mo-Au mineralisation, advanced argillic alteration and quartz-sulphide-gold-anhydrite veins in the Thames District, New Zealand - R. Brathwaite; M. Simpson; K. Faure; D. Skinner (Mineralium Deposita, 2001)

The Importance of Nitrogen Oxides for the Exceedance of Critical Thresholds in the Nordic Countries - M. Johansson; R. Suutari; J. Bak; G. Lövblad; M. Posch; D. Simpson; J.-P. Tuovinen; K. Tørseth (Water, Air, & Soil Pollution, 2001)

Estimation and significance testing of cross-correlation between cerebral blood flow velocity and background electro-encephalograph activity in signals with missing samples - D. M. Simpson; A. F. C. Infantosi; D. A. Botero Rosas (Medical & Biological Engineering & Computing, 2001)

Estimating normal and pathological dynamic responses in cerebral blood flow velocity to step changes in end-tidal pCO2 - D. M. Simpson; R. B. Panerai; D. H. Evans; J. Garnham; A. R. Naylor; P. R. F. Bell (Medical & Biological Engineering & Computing, 2000)

Somaclonal variation in cryopreserved embryogenic clones of white spruce [ Picea glauca (Moench) Voss.] - L. L. DeVerno; Y. S. Park; J. M. Bonga; J. D. Barrett; C. Simpson (Plant Cell Reports, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Announcement - P. D. Markel; B. Bennett; M. A. Besson; L. Gordon; V. J. Simpson; T. E. Johnson (Mammalian Genome, 1997)

Erratum - P. D. Markel; B. Bennett; M. A. Besson; L. Gordon; V. J. Simpson; T. E. Johnson (Mammalian Genome, 1997)

Partial purification and characterisation of an aromatic amino acid aminotransferase from mung bean (Vigna radiata L. Wilczek) - R. M. Simpson; H. M. Nonhebel; D. L. Christie (Planta, 1997)

Why do some females reject males? The molecular basis for male-specific graft rejection - D. M. Scott; I. E. Ehrmann; P. S. Ellis; P. R. Chandler; E. Simpson (Journal of Molecular Medicine, 1997)

Restriction site polymorphism in genes encoding type 2 but not type 1 gonococcal IgA1 proteases - M. H. Mulks; D. A. Simpson; R. J. Shoberg (Antonie van Leeuwenhoek, 1987)

Mount elgon bat virus: A hitherto undescribed virus from Rhinolophus hildebrandtii eloquens K. Anderson - D. Metselaar; M. C. Williams; D. I. H. Simpson; R. West; F. A. Mutere (Archives of Virology, 1969)